Experimental investigation based on MCDM optimization of electrical discharge machined Al-WC–B4C hybrid composite using Taguchi-MARCOS method. (2023) - Biswal, Smrutiranjan; Sahoo, Bibhuti Bhusan; Jeet, Siddharth; Barua, Abhishek; Kumari, Kanchan; Naik, Bibekananda; Pradhan, Swastik
Abstract: Electrical discharge machining is a recognised non-traditional machining practise capable of accurately engineering components with multi-faceted contours. Through the stir casting process, two different aluminium alloys (Al 7175 and Al 6061)-based hybrid nanocomposites were developed and strengthened with tungsten carbide (WC) at 10 % and boron carbide (B4C) at 10 % in the current study. After mechanical characterization of the composites, electrical discharge machining (EDM) has been piloted on specimens to scrutinise the machining parameters. Taguchi's design of the L9 orthogonal array was implemented to conduct experiments with the help of three EDM parameters such as voltage applied, current applied, and pulse-on time to find out their effects on machining time taken, surface roughness, along with the material removal rate. Optimization has been carried out using MARCOS technique (Measurement Alternatives and Ranking according to Compromise Solution), and optimal results have been confirmed through confirmatory tests. It is found that voltage and current are the most noteworthy factors in EDM machining of the Aluminium alloy composite. Also, it was found that the tensile along with ultimate tensile strength of Al6061-WC-B4 C and Al7175-WC-B4 C composites were found to be 17.810KN, 86.30KN, and 51.746 N/mm 2, 271.520 N/mm 2 respectively.